2000
DOI: 10.1017/s0958344000000215
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Information and Communication Technology (ICT) to language learning environments or the mystery of the secret agent

Abstract: In this paper, E. Esch and C. Zähner argue that the learners themselves are the key agents in the construction of new language learning environments. Learners differ in their ability to import new elements – such as ICTs – into their model of what constitutes an appropriate language learning environment. It is argued that accessibility, autonomy, ‘reflectivity’ and interactivity are conditions which must be met if ICTs are to become truly relevant to language learners. The way these principles have been g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Beyond the practical developmental considerations presented here and hopes for future applications, this paper strove to highlight both the nature and the impact of the research undertaken through its methodology, its findings and its influence on the design. It corroborates the view expressed by Esch and Zähner (2000) and Levy (1999), amongst others, that future CALL developments and, in particular, Web-based language learning deliveries can only be successful on the basis of a close involvement between language teachers and learners. CALL deliverables should not simply be seen in terms of finished products destined for immediate and compulsory consumption by students, assuming designers know best, but as a means of exploring new forms of interaction at the level of the interface as well as within the language learning process itself.…”
Section: Resultssupporting
confidence: 87%
“…Beyond the practical developmental considerations presented here and hopes for future applications, this paper strove to highlight both the nature and the impact of the research undertaken through its methodology, its findings and its influence on the design. It corroborates the view expressed by Esch and Zähner (2000) and Levy (1999), amongst others, that future CALL developments and, in particular, Web-based language learning deliveries can only be successful on the basis of a close involvement between language teachers and learners. CALL deliverables should not simply be seen in terms of finished products destined for immediate and compulsory consumption by students, assuming designers know best, but as a means of exploring new forms of interaction at the level of the interface as well as within the language learning process itself.…”
Section: Resultssupporting
confidence: 87%
“…In conclusion, the endeavor of ICT integration augments the exigency for specialized teacher training to ensure that ICT is employed in the most proficient and easily adaptable fashion by taking into account future users' views and requirements in the design and development process if the training of foreign language teachers is to benefit from web-based delivery (Sercu & Peters, 2002). As a result, teachers will benefit from this experience and take a step forward in their individual professional growth along with effectively catering for their students' needs and contributing to education at a global degree (Esch & Zähner, 2000). With respect to the positive impact of ICTs on ELTs Jayanthi and Kumar (2016) mention several factors including the fact that ICTs can help teachers in preparing, producing, storing and retrieving learning materials that can be interactive and available in multiple formats.…”
Section: Theoretical Implications For the Training Of The Teachersmentioning
confidence: 99%
“…Computermediated communication researchers found that L2 lexical knowledge is critical in online interaction between native and non-native speakers since it is the primary trigger for the meaning negotiating process [22,24,26]. To reduce speaking anxiety and enhance collaborative contact, opportunities for creating good relationships should be provided by having participants meet each other in person initially [32,33]. Most of Lee's 2007 study participants did not hire body gestures or voices to convey meaning and compensate for their language failures [21].…”
Section: Literature Reviewmentioning
confidence: 99%